Os projetos de lei municipal sobre violência da cidade de São Paulo (1991 a 2003): uma caracterização comportamental - Macedo, Lívia Maria Demarchi Santos de (2004)
The City of São Paulo is known, among other hallmark characteristics, as the third largest and on of the most violent cities in the world. Based on the concept of the "violence" phenomenon for radical behaviorism, on the discussion initiated by Skinner about the Governmental Agency, about laws as an instrument of social control and related literature, a description was performed of the law projects developed between 1991 and 2003 by law makers in the Municipal Chamber of São Paulo (MCSP) from four different aspects: institutional, violence to be avoided, proposed action and the expected results. The main material utilized were law projects (law text and justification)and the respective in-process reports issued by the database of the Municipal Chamber of the City of São Paulo. 73 law projects were found indexed with the key word "violence" of which 67 (selection I) were described according to all the aspects previously mentioned. Another 87 (selection II) projects indexed with the key word "safety" were discussed only on their "institutional" aspects. The results showed that there is a small number of projects indexed like this, in relation to the total number of MCSP'5 laws, of which only 15,6% of the selected ones were approved. There is also a high number of authors in individual projects and a small number of authors with systematic production in the period. With regards to the political parties' participation in the proposal of these projects the results indicate a high variation. "Crimes and felonies" and the violence happening within "Special Circumstances" were the most mentioned problems under violence. About 1/3 of the projects do not specify the participants in the violence and almost half do not describe the place where the violence occurs. The majority of the actions dealing with violence are characterized by those who were already victimized by violence or to promote "information:(including "commemorative"dates) to the population. Entities responsible for these actions are in the majority Government Agents and/or (in joint ventures) private initiative.Half of the projects do not specify consequences for (not) complying with the law rand only two projects specify benefits for complying with i1.In spite of this, more than half the projects describe as expected outcome: "reduction of crime rates" or "information". Considerations determined by pre-supposed ideas in behavior science about possible social implications of projects that are too generic in the definition of the problem and confrontation action were discussed